Oracle - Olde Heuvelt, Thomas, 1983- (Nightfire, Tor Publishing Group, 2024)
On a foggy winter morning two children discover the impossible: the wreck of an eighteenth-century ship stranded in a field. One enters the hatch on the deck and is never seen again. And she isn't the last to disappear. Soon a government agency begins to investigate, determined to uncover the ship's secrets before a media storm erupts. They enlist Robert Grim, a retired specialist of the occult, to unravel the mystery, who soon realises the ship could be a harbinger of an ancient doom awakened under the sea. In a maelstrom of international intrigue and pure terror, Grim must race against time as he comes face to face with an open doorway to the apocalypse.